Finite Element Modeling of Magnitude and Location of Brain Micromotion Induced Strain for Intracortical Implants - Al Abed, Ali; Amatoury, Jason; Khraiche, Massoud (Frontiers in Neuroscience, 2022)
Advances in neuroprosthetic intervention rely heavily on chronic integration of Intracortical Mi-croelectrode. Brain micromotion-induced stress remains one of the main determinants of implant life as high stress leads to tissue injury which in turn leads to an immune response and significant reduction in the nearby neural population and subsequent electrical isolation of the implant. The impact of micromotion on tissue-induced strain is not very well studied. In this work, we develop a finite element model of the probe-tissue interface in the brain to study the effect of the complete range of implant micromotion, implant thickness, and material properties on the strain levels in-duced in brain tissue. Our results showed that for stiff implants, the strain magnitude is depend-ent on the magnitude of the motion, where a micromotion increase from 1 μm to 10 μm induced an increase in the strain by an order of magnitude while for higher displacement over 10 μm the change in the strain was relatively smaller. We also showed that displacement magnitude has no impact on the location of maximum strain and addressed the conflicting results in the literature. Further, we explored the effect of several materials including silicon, polyimide (PI), polyvinyl acetate nanocomposite (PVAc-NC) on the magnitude, location, and distribution of strain. Finally, we showed that strain distribution across cortical implants was in line with published results on the size of the typical glial response to the neural probe, further reaffirming that strain can be a precursor to the glial response.